Psychometric evaluation of the Questionnaire about the Process of Recovery (QPR) - Williams, Julie; Leamy, Mary; Pesola, Francesca; Bird, Victoria; Le Boutillier, Clair; Slade, Mike (Royal College of Psychiatrists, 2015)
Background: Supporting recovery is the aim of national mental health policy in many countries, including England. There is a need for standardised measures of recovery, to assess policy implementation and inform clinical practice. Only one measure of recovery has been developed in England: the Questionnaire about the Process of Recovery (QPR) which measures recovery from the perspective of adult mental health service users with a psychosis diagnosis. Aims: To independently evaluate the psychometric properties of the 15-item and 22-item versions of QPR. Method: Two samples were used: Dataset 1 (n=88) involved assessment of QPR at baseline, two weeks and three months. Dataset 2 (n=399; ISRCTN02507940) involved assessment of QPR at baseline and one year. Results: For the 15-item version, internal consistency was 0.89, convergent validity was 0.73, test-retest reliability was 0.74 and sensitivity to change was 0.40. Confirmatory factor analysis showed the 15-item version offered a good fit. For the 22 item version comprising two sub-scales, the Interpersonal sub-scale was found to under-perform and the Intrapersonal sub-scale overlaps substantially with the 15 item version. Conclusions: Both the 15-item and the Intrapersonal sub-scale of the 22-item versions of the QPR demonstrated satisfactory psychometric properties. The 15-item version is slightly more robust and also less burdensome, so it can be recommended for use in research and clinical practice. Declaration of interest: None.